SYNTHESIS, ELECTRONIC AND SPECTRAL PROPERTIES OF NEW 1,3,4-THIADIAZOLE COMPOUNDS AND THE SPECTRAL ANALYSIS OF THEIR CONFORMERS USING DENSITY FUNCTIONAL THEORY - Çavuş, Muhammet Serdar; Çelik, Tuğba (Sociedade Brasileira de Quimica (SBQ), 2018)
In this study, new 1,3,4-thiadiazole compounds were synthesised and characterised by FT-IR, 1H-NMR, UV-vis spectroscopy and elemental analysis, Furthermore, the relationship between the electronic and spectral data of the 16 conformers of each compound was investigated by theoretical calculations; the theoretical data were compared with the experimental results. The B3LYP hybrid functional level with a 6-311++g(2d,2p) basis set was used to obtain the ground state geometries, frontier molecular orbital energies, band gap energies and chemical reactivity parameters and to perform a spectral analysis of the compounds. Significant correlations were calculated between the minimum molecular energy and the N-H and C=O vibrational frequencies and the NH proton chemical shifts of the conformers. The charge density on the nitrogen atom and the delocalisation index of the highly polar N-H covalent bond were investigated by quantum theory of atoms in molecules. The effect of conformer structure on the theoretical results and its role in interpreting the experimental data were presented, and it was theoretically shown that the activity degree of the non-aromatic electronegative atoms or groups of atoms in the intramolecular interaction was a very important factor in determining the electronic and spectral properties of each compound.
Keywords: conformational effect; Chemistry; conformers; thiadiazole; QD1-999; Density Functional Theory; spectral analysis; 7. Clean energy